CLINICAL PRESENTATION AND DISEASE COURSE OF USHER SYNDROME BECAUSE OF MUTATIONS IN MYO7A OR USH2A. Issue 8 (August 2017) - Testa, Francesco; Melillo, Paolo; Bonnet, Crystel; Marcelli, Vincenzo; de Benedictis, Antonella; Colucci, Raffaella; Gallo, Beatrice; Kurtenbach, Anne; Rossi, Settimio; Marciano, Elio; Auricchio, Alberto; Petit, Christine; et al.
Abstract : Purpose: To evaluate differences in the visual phenotype and natural history of Usher syndrome caused by mutations in MYO7A or USH2A, the most commonly affected genes of Usher syndrome Type I (USH1) and Type II (USH2), respectively. Methods: Eighty-eight patients with a clinical diagnosis of USH1 (26 patients) or USH2 (62 patients) were retrospectively evaluated. Of these, 48 patients had 2 disease-causing mutations in MYO7A (10 USH1 patients), USH2A (33 USH2 patients), and other USH (5 patients) genes. Clinical investigation included best-corrected visual acuity, Goldmann visual field, fundus photography, electroretinography, and audiologic and vestibular assessments. Longitudinal analysis was performed over a median follow-up time of 3.5 years. Results: Patients carrying mutations in MYO7A had a younger age of onset of hearing and visual impairments than those carrying mutations in USH2A, leading to an earlier diagnosis of the disease in the former patients. Longitudinal analysis showed that visual acuity and visual field decreased more rapidly in subjects carrying MYO7A mutations than in those carrying USH2A mutations (mean annual exponential rates of decline of 3.92 vs. 3.44% and of 8.52 vs. 4.97%, respectively), and the former patients reached legal blindness on average 15 years earlier than the latter. Conclusion: The current study confirmed a more severe progression of the retinal disease in USH1 patients rather than in USH2 patients. Furthermore, most visual symptoms (i.e., night blindness, visual acuity worsening) occurred at an earlier age in USH1 patients carrying mutations in MYO7A . Abstract : The current longitudinal study confirmed a more severe progression of the retinal disease in Usher syndrome Type 1 than in Usher syndrome Type 2 patients. Moreover, most visual symptoms occurred at an earlier age in Usher syndrome Type 1 patients carrying mutations in MYO7A .